Role of Religiosity Support in Generating Employee’s Positive Work Behaviour - Tri Wulida Afrianty (Universitas Pendidikan Ganesha, 2020)
AbstractThe purpose of this research is to examine the impact of individual religiosity as well as religiosity support on employee’s organizational commitment. This research is located in two Syariah Banking in Malang, East Java. A quantitative approach was undertaken in this research. The hypotheses were developed heavily based on Social Exchange Theory. The main finding of this research provides support to the theory, that is religiosity support (as a form of positive behaviour, managed by the organizations) has a significant impact in increasing employees’ organizational commitment